An Aristotelian Realist Philosophy of Mathematics - Franklin, J. author. aut Link
X, 308 p.
Keywords: Mathematics is as much a science of the real world as biology is. It is the science of the world's quantitative aspects (such as ratio) and structural or patterned aspects (such as symmetry). The book develops a complete philosophy of mathematics that contrasts with the usual Platonist and nominalist options.